Ultra-processed food consumption and the risk of overweight and obesity in adolescents: A systematic review and meta-analysis - Mekuriaw Nibret Aweke; Habtamu Wagnew Abuhay; Miteku Andualem Limenih; Anas Ali Alhur; Nebebe Demis Baykemagn; Gebrie Getu Alemu; Makda Fekadie Tewelgne; Tirualem Zeleke Yehuala (PLoS ONE, 2026)
Introduction Overweight and obesity during early life increase the risk of premature morbidity and mortality. Adolescent obesity raises the likelihood of developing cardiovascular risk factors, including prediabetes, type 2 diabetes, dyslipidemia, hypertension, liver disease, and metabolic syndrome. Sedentary lifestyles and unhealthy diets are major contributors, with one of the fastest-growing unhealthy eating patterns being the consumption of ultra-processed foods (UPFs). No systematic review and meta-analysis has specifically examined the association between UPF consumption and overweight/obesity in adolescents. Objective To systematically review and conduct a meta-analysis of available evidence on the association between UPF consumption and overweight or obesity among adolescents. Methods We searched PubMed, ScienceDirect, HINARI, Google, and Google Scholar for primary studies reporting UPF consumption and overweight/obesity outcomes in adolescents, without restrictions on language or study period. Study quality was assessed using the Newcastle–Ottawa Scale. Heterogeneity was evaluated using Cochrane’s Q test and the I² statistic. Publication bias and small-study effects were assessed using Egger’s regression test (p < 0.05). A random-effects model estimated pooled associations. Results Twenty-three studies involving 155,000 adolescents were included. Adolescents with higher UPF consumption had 63% greater odds of overweight or obesity compared with those with lower intake (OR = 1.63; 95% CI: 1.36–1.95). Conclusion High UPF consumption is associated with an increased risk of overweight and obesity among adolescents. Public health strategies targeting reduced UPF intake and promotion of healthier diets should be prioritized to prevent adolescent overweight/obesity and associated health risks.